Comparison of different pretreatments on the synergistic effect of cellulase and xylanase during the enzymatic hydrolysis of sugarcane bagasse. Issue 54 (31st August 2018) - Huang, Chao; Zhao, Cheng; Li, Hailong; Xiong, Lian; Chen, Xuefang; Luo, Mutan; Chen, Xinde
Abstract : The synergistic effects between cellulase and xylanase were substrate and time specific during the hydrolysis of pretreated SCB. Abstract : Sugarcane bagasse (SCB) substrates with different chemical compositions were prepared by different pretreatments including dilute acid (DA), acidic sodium chlorite (ASC), alkali solution (AS), and alkali hydrogen peroxide (AHP). The compositions and chemical structures of pretreated SCB were characterized by HPLC, FTIR, XRD, and SEM. The addition of xylanase can significantly boost cellulase to hydrolyze cellulose and xylan especially for AS and AHP treated substrates. The obvious linear relationships between lignin removal and substrate digestibility were observed. ASC treated substrates obtained the highest digestibility (98.87%) of cellulose due to sufficiently removing lignin from SCB, whereas AHP treated substrates achieved the highest digestibility (84.61%) of xylan by cleaving the acetyl group on xylan and extending delignification. It was found that the synergistic effects between cellulase and xylanase were substrate and time specific. The better degree of synergy for the sugar production was in the initial hydrolysis stage but decreased in the later hydrolysis stage.